2021
DOI: 10.1371/journal.pone.0261120
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Data-based Instruction (DBI) for Students with Learning Difficulties in Korea: A Single-subject Meta-analysis

Abstract: Data-based instruction (DBI) is an ongoing process to utilize students’ data for determining when and how to intensify intervention. It is an educational approach that is suggested as effective to enhance achievements of struggling learners, particularly for those who did not respond to intensive intervention in usual ways. In Korea, DBI was introduced and applied for students with learning difficulties especially since 2000 when the first Korea curriculum-based measurement (CBM) was developed as the name of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…After an adjustment is implemented, the process is repeated to continue monitoring student progress. Metaanalyses of DBI effectiveness support its use for improving academic performance across content areas (Jung et al, 2018;Kim & Choi, 2021).…”
Section: A Systematic Review Of Cbm Content In Practitioner-focused J...mentioning
confidence: 96%
“…After an adjustment is implemented, the process is repeated to continue monitoring student progress. Metaanalyses of DBI effectiveness support its use for improving academic performance across content areas (Jung et al, 2018;Kim & Choi, 2021).…”
Section: A Systematic Review Of Cbm Content In Practitioner-focused J...mentioning
confidence: 96%
“…We selected intervention studies on SEL programs delivered to children and adolescents before adulthood and measuring their effectiveness quantitatively by following procedures (Fig 1). First, relevant studies were identified through three Korean major research data repositories, which are the most frequently used database to conduct systematic review on Korean articles [8]: RISS (Research Information Sharing Service; https://www.riss.kr), KISS (Korean studies Information Service System; https://kiss.kstudy.com), and Nurimedia DBpia (https:// www.nurimedia.co.kr). We set social-emotional as a term necessary to be included in the title, abstract, and keywords from each study, with combination of following nouns such as learning, education, and competence.…”
Section: Literature Searchmentioning
confidence: 99%
“…However, individual SEL programs do not always show the same astonishing improvement in students' socioemotional competencies unless implemented effectively, with high-quality, evidence-based instructions [5,6]. In educational practice, since teachers are required to use instructions scientifically proven effective, it is necessary for researchers to constantly identify and implement evidence-based practice (EBP) [7,8]. In order to investigate EBP of a certain kind of educational program, it is first necessary to identify the considerable effectiveness of that program across various participants, formats, and educational settings [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation